PERFORMANCE IMPROVEMENT DISTRICT BELINYU GUARD PT.TIMAH IN THE PRESENCE OF GIVING BONUS COMPENSATION - EDWIN TRIGUNAWAN; ERWIN SUGIANTO (Journal of Business Studies and Management Review, 2019)
The purpose of this study is the first one to know is there an increase in the performance of the security guard with their bonuses PT.Timah compensation, the latter in order to give an idea of the performance of the security PT.Timah so as to provide input to the leading companies in making decisions regarding performance improvement and compensation in accordance with the expectations of the workers. This research method is descriptive and qualitative analysis. Resource persons from this study were drawn at random from among the guard PT.Timah, with the number of respondents as many as 10 people. The results obtained from this study is the performance of a high enough security PT.Timah although bonus compensation given by the company is not as expected the guards,